Switch from connection ductility to reinforcement ductility with curvature reversal in timber-concrete composites. (30th December 2019) - Sebastian, W.M.
Highlights: Mesh connections are very effective in fully cracked negative curvature zones. Thus connections more than doubled member stiffness under negative curvature. Ductility obtained in TCCs under both positive and negative curvatures. Ductility source switched from connection to rebar yield with curvature reversal. Transformed section theory reasonably predicts negative curvature zone behaviour. Abstract: While multi-span continuity can be used to structurally enhance timber-concrete composites (TCCs), there has been scant research into the associated nonlinear load responses particularly of the resulting TCC zones under negative curvature. Consequently this paper presents tests to failure of TCC specimens using hardwood laminated veneer lumber joists and steel mesh connectors, one specimen (TP) under positive curvature, the other (TN) under negative curvature. It was found that the mesh connectors enabled high levels of slab-joist interaction not only in TP where the slab was almost uncracked, but also in TN where the slab exhibited pronounced cracking. Such distinct interaction enabled TN and TP to develop more than twice and six times, respectively, the stiffness of the joist acting alone. Both TCC members exhibited encouraging ductility, the source of which switched from connection yield distributed along half the span in TP to steel rebar yield concentrated at midspan in TN. TP displayed deflection (global) and curvature (local) ductility near-plateaux over ranges close to or exceeding the corresponding elastic ranges, while for TN the ductility was manifest as low tangent stiffness regimes over deflection and curvature ranges generously exceeding the corresponding elastic ranges. A conspicuous residual hinge at midspan in TN and significant residual end slip in TP provided visual evidence of the ductility. These observations address the issue of TCC connection effectiveness in cracked concrete that has emerged from updating EC5. Crucially, the ductility of TN is predicated on the hardwood's high strain to fracture in flexure, which ensured that extensive rebar plasticity preceded failure of the timber.